IMPROVING STUDENTS’ WRITING USING GUIDED-QUESTION TECHNIQUE - Suryani Suryani; Naulan Millatina; Fidyati Fidyati; Syarifah Rahmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
This research aims at knowing whether guided-question technique can improve students’ ability in writing narrative text and also finding out the students’ responses in applying guided-question technique in their writing. This experimental research was conducted at SMPN 1 Indrapuri. The sample of the research was class VIII-1 (experimental class) and class VIII-2 (control class), with the number of student was 40 students. In collecting the data, tests and questionnaire were used. Based on the result of data analysis, the students of the experimental class achieved the improvement from 65,23 to 76,66, while the control class students only showed a slightly improvement (from 65 to 66). It can be concluded that guided-question technique can improve students’ ability in writing narrative text. The students were able to generate ideas and details by asking some questions about the subject in their writing process. The questionnaire results revealed that guided-question technique can motivate and make the students are interested in writing. So, the teacher of the school may use this technique in improving the students’ ability in writing narrative text.